A cellular automaton based heuristic for multi-level lot sizing and scheduling - Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1993)
Cellular automata were used to model and to simulate phenomena in the area of physics, biology and medicine. In this paper it is now shown how the idea of cellular automata can be applied to optimization problems as well. As an example a cellular automaton is used as a basis for solving multi-level lot sizing and scheduling problems to suboptimality. We will furthermore give an outline of a proof that any genetic algorithm can be interpreted as a cellular automaton.
Keywords: 650; Production planning; lot sizing; scheduling; PLSP; multi-level; cellular automata; hybrid heuristics; genetic algorithms; Produktionssteuerung; Bioökonomik; Theorie